Profil Klinikopatologik Karsinoma Payudara Invasif Metastasis Jauh di Departemen Patologi Anatomik FKUI/RSCM Tahun 2019 - Kurnianingrum, Laurencia Leny; Tjahjadi, Hartono (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2022)
BackgroundInvasive breast carcinoma (IBC) is the highest incidence and is the leading cause of malignancy-related death in women in theworld. Bones are the most common sites of IBC metastases. This study aims to provide clinical and histological characteristic datain cases of distant metastastic IBC in the Anatomical Pathology Department, Faculty of Medicine, Universitas Indonesia, Dr. CiptoMangunkusumo General Hospital (PA-FKUI/RSCM).MethodsThis is descriptive research with cross-sectional design, using secondary data from the archives of PA-FKUI/RSCM, starting fromJanuary 1, 2019 to December 31, 2019.ResultsDistant metastases of IBC was found 65.2% as bone metastases, 46.1% as pulmonary metastases, 26.1% as liver metastases, and8.7% as brain metastases. The largest age group was 40-59 years, median age was 49 years with range 27-78 years. The mostcommon of the classification of primary tumor size was 54.8% T4, and 87% unilateral cases. Most histologic subtypes were 90.4%cases no special type, then lobular and mucinous subtypes. Lymphovascular invasion was 24.3% cases. The most commonmolecular subtype was luminal B Luminal and mostly as bone metastases and triple negative breast cancer (TNBC) in lungmetastases. The greatest histological grade was grade 2.ConclusionBone was the most common IBC metastatic. The most common of the classification of primary tumor size was T4 and histologicsubtype was no special. Luminal B was the most common molecular subtypes and the highest was bone metastases.